2014
DOI: 10.1080/13607863.2014.917606
|View full text |Cite
|
Sign up to set email alerts
|

Santa Clara Strength of Religious Faith Questionnaire: psychometric analysis in older adults

Abstract: Objectives To assist researchers and clinicians considering using the Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) with older-adult samples, the current study analyzed the psychometrics of SCSRFQ scores in two older-adult samples. Method Adults age 55 or older who had formerly participated in studies of cognitive-behavioral therapy for anxiety and/or depression were recruited to complete questionnaires. In Study 1 (N = 66), the authors assessed the relations between the SCSRFQ and other mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
(70 reference statements)
2
15
0
Order By: Relevance
“…Strength of faith could have been assessed using specific questionnaires such as the Santa Clara Strength of Religious Faith Questionnaire 40,41 or the Revised Religious Fundamentalism Scale 42 . However, this approach would have been too long for participants and not well adapted to this survey, as these questionnaires are very focused on religion, while religion was not the main field of this study, and is a very sensitive subject in French population.…”
Section: Discussionmentioning
confidence: 99%
“…Strength of faith could have been assessed using specific questionnaires such as the Santa Clara Strength of Religious Faith Questionnaire 40,41 or the Revised Religious Fundamentalism Scale 42 . However, this approach would have been too long for participants and not well adapted to this survey, as these questionnaires are very focused on religion, while religion was not the main field of this study, and is a very sensitive subject in French population.…”
Section: Discussionmentioning
confidence: 99%
“…The original and brief versions of the SCSRFQ are expected to have a unidimensional structure and high reliability estimates, as indicated by the literature (Plante 2021). Also, the SCSRFQ score is expected to correlate positively with life satisfaction (Cummings et al 2015;Freiheit et al 2006;Hebert et al 2009;Wnuk 2017). Although there are no studies relating COVID-19 anxiety and faith strength, a positive relationship is expected, as noted by previous studies relating the latter variable to general anxiety symptoms (Plante et al 2001;Plante et al 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Several studies, in different cultural contexts, have shown that the SCSRFQ is a unidimensional measure of religious faith, with adequate reliability, that presents significant relationships with other variables such as religious life and orientation, intrinsic religious motivation, social provisions, social desirability, anxiety, emotional control, self-righteousness, optimism, spiritual experience, religious coping, negative and positive affect, religiosity and spirituality, spiritual well-being, depression and life satisfaction, among others (Akin et al 2015;Cummings et al 2015;Dianni et al 2014;Freiheit et al 2006; Koukounaras Liagkis and Ktenidis 2021; Lewis et al 2001;Pakpour et al 2014;Plante and Boccaccini 1997;Plante et al 1999;Sherman et al 1999;Sherman et al 2001;Wnuk 2017). Seeking to facilitate the use of the SCSRFQ in epidemiological research and the evaluation of patients with medical illnesses, a study conducted with samples of university students, women with cancer or cancer screening patients, and healthy women in a clinical setting developed a brief version consisting of items 2, 4, 5, 8, and 10 of the original questionnaire (SCSRFQ-SF;Plante et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review, Greggo and Lawrence (2012) identified 21 measures of religiousness and spirituality with reasonable psychometric properties and amenable to clinical use. One of the instruments reported was the Santa Clara Strength Of Religious Faith Questionnaire (SCSRFQ; Plante & Boccaccini, 1997), which has been extensively used, with diverse sociodemographic samples, including older adults (Cummings et al, 2015), to assess strength of religious faith, and its relation to psychological and health outcomes (Plante, 2010). There is substantial evidence of this instrument's psychometric qualities and usefulness as a religion assessment tool, with studies showing high positive correlations between the SCSRFQ and other religious faith instruments, moderate positive correlations with measures such as hope, optimism, and perceived coping, and negative correlations with low self-esteem and anxiety (Plante, 2010).…”
Section: Introductionmentioning
confidence: 99%